Occupational Health Hazards among Rural Women in Selected Animal Husbandry Operations - Tripathi, Hema; pandey, Rakesh; Singh, Mukesh; Singh, Bharti (Indian Journal of Extension Education, 2013)
Afield experiment was done with 60 rural women selected from 6 different villages within the age group of 20-45 years to  determine their occupational workload and muscular stress based on their physiological responses while performing  selected six drudgery prone/strenuous animal husbandry activities with the use of existing tool, equipments and  techniques. The study revealed that physiological workload, total cardiac cost of work, physiological cost of work of rural  women, their perceived exertion and reduction in the grip strength while performing the activities was very high for all the  selected activities. The highest drudgery oriented activity was the chaffing followed by collection and disposal of dung  and making of cowdung cakes revealing the fact that all the activities taken under the study were highly drudgery prone.  There is a need to aware and motivate the rural women to adopt the improved tools, techniques and equipments to reduce  physiological cost of work and drudgery in animal husbandry operations which in turn will influence work efficiency and  work productivity.
Keywords: Animal husbandry; drudgery; ergonomics; health hazards; rural women